Microglial Engulfment of Spines in the Ventral Zona Incerta Regulates Anxiety-Like Behaviors in a Mouse Model of Acute Pain - Farzinpour, Zahra; Liu, An; Cao, Peng; Mao, Yu; Zhang, Zhi; Jin, Yan (Frontiers in Cellular Neuroscience, 2022)
Abstract. Although activation of microglial cells is critical in developing brain disorders, their role in anxiety-like behaviors in pain is still vague. This study indicates that alteration of microglia’s neuronal spine engulfment capacity in ventral Zona Incerta (ZIV) leads to significant pain and anxiety-like behaviors in mice one-day post-injection of Complete Freud’s Adjuvant (CFA1D). Performing whole-cell patch-clamp recordings in ZIVGABA neurons in brain slices, we observed decreased neuronal activity in ZIvGABA and reduced frequency of the miniature excitatory postsynaptic currents (mEPSCs) in CFA1D mice, compared with the control mice. Besides, chemogenetic activation of ZIVGABA significantly relieved pain and anxiety-like behaviors in CFA1D mice with increased hyperactivity in ZIVGABA. Conversely, in naïve mice, chemogenetic inhibition of ZIVGABA induced pain and anxiety-like behaviors with decreasing neural hyperactivity in ZIVGABA. Interestingly, we found that ZIVMicroglia were notably activated, with density and morphology alterations. Imaging the CFA1D brain slices revealed that inflammation escalates the extent of microglial engulfment spines in ZIV. Furthermore, when the ZIV Microglia of CFA1D-treated animals were chemically inhibited by intra- ZIV minocycline injection, the decreased ZIVGABA neuronal excitability was reversed, and CFA1D mice did not reveal pain sensitization and anxiety-like behaviors. Conclusively, our results provide novel insights that inflammation produces dysregulation of microglial engulfment capacity, which encodes maladaptation of ZIVGABA, thus promoting the development of anxiety-like behaviors in pain.